HUBUNGAN DIAGNOSIS PENYAKIT DENGAN PEMBERIAN RUJUKAN PASIEN BPJS DI PUSKESMAS PRINGGASELA UTAMA TAHUN 2022 - Amalia Rizkiani; Abdul Aziz Fatriyawan (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2022)
Health services are carried out in stages starting from the first level of health services, second level health services (district general hospitals) can only be provided upon referral from first level health services, third level health services (provincial or central general hospitals) can only be provided for referrals from second-level or first-level health services, except in emergencies. This study aims to determine the relationship beteen disease diagnosis and the provision of referrals for BPJS patients at the pringgasela utama public health center in 2022. This research method uses analytical observational. The population in this study were outpatients totaling 97 people. The technique used is observation, documentationdata taken using a questionnaires shon in the table and analyzed using the contingency coefficient test. The result of this study obtained a probability value (p value) for the contingency coefficient test, the value = 0,000 < α 0,05, (significant), meaning there is a significant relationship beteen disease diagnosis and the provision of BPJS patient referral at the Pringgasela Urtma healt center in 2022.